FACTORS WHICH AFFECTING THE BRANDSWITCHING OF ONLINE FOOD DELIVERY USERS (Research on Students of Lampung University) - Zuhara, Hafazah; S.Sos M.A, Hartono; Aprilia., S.A.B., M.Si., Hani Damayanti (Jurnal Kompetitif Bisnis, 2022)
Abstract The purpose of this study was to determine partially and simultaneously the effect of price and service quality on brand switching. The sampling technique in this study used non-probability sampling with purposive sampling method. Collecting data using a questionnaire obtained 100 respondents.. The data analysis technique used multiple regression analysis with IBM 25 program testing tools. Partially shows that the price variable has a significant effect and has a positive direction on brand switching and the service quality variable has a significant effect and has a positive direction on brand switching. Based on the F (simultaneous) test, it shows that the price and service quality variables have a simultaneous effect on brand switching. Keyword: Brand Switching, Price, and Quality of Service.